Tracing mantle components and the effect of subduction processes beneath the northern Antarctic Peninsula. (15th February 2023) - Anderson, D.W.; Saal, A.E.; Lee, J.I.; Mallick, S.; Riley, T.R.; Keller, R.A.; Haase, K.M.
Abstract: Understanding subduction processes is critical in assessing the long-term evolution of the upper mantle and continental crust. We present new geochemical data on glassy submarine lavas from the Bransfield Strait, the Phoenix and West Scotia ridges, and previously unpublished data of marine sediments from atop the Phoenix Plate. We combined new and published geochemical data from across the northern sector of the Antarctic Peninsula to unravel both large-scale mantle composition and flow across the region. The geochemistry of Phoenix and West Scotia Ridge basalts supports the hypothesis that both ridges are underlain by Pacific MORB mantle, brought into the region through the eastward expansion of the Scotia Plate. Comparisons among lavas from the Phoenix/West Scotia ridges, the South Shetland Islands volcanic arc, and the Bransfield Strait/Prince Gustav Rift back-arc region reveal that the Pacific upper mantle flowed into the mantle wedge and was subsequently modified by subduction processes. The compositions of Bransfield Strait lavas range from strongly subduction-influenced near the strait's center to akin to Phoenix Ridge MORB toward the strait's edges. This suggests that the Phoenix MORB mantle has flowed around the slab edges into the mantle wedge, diluting the subduction signal and focusing the subduction-modified mantle towards the center of the strait. Monte Carlo simulations indicate that mixing of Phoenix MORB mantle with 0 to 3 % subduction component having a fluid/sediment ratio of ∼1 can explain the compositional range in the Bransfield Strait. Furthermore, our modeling suggests the presence of a more depleted Phoenix MORB mantle beneath the South Shetland Islands modified by the addition of ∼3 % subduction component with a fluid/sediment ratio ranging from ∼0.18 to 4. The increase in fluid/sediment ratios in the South Shetland Island lavas corresponds to a spatiotemporal progression of volcanism from the southwest (40–140 Ma) to the northeast (30–60 Ma). Finally, we have identified a set of lavas with unique trace element and isotope compositions typical of alkaline volcanism found across other parts of the Antarctic Peninsula. Surprisingly, we find occurrences of these lavas on both sides of the South Shetland Trench, suggesting the presence of a distinct enriched source in the upper mantle throughout the region.